2014
DOI: 10.1039/c4tc01790k
|View full text |Cite
|
Sign up to set email alerts
|

Reduced roughness for improved mobility in benzodipyrrolidone-based, n-type OFETS

Abstract: Six phenyl-flanked benzodipyrrolidone-based copolymers are designed, synthesised and characterised. Three exhibit backbone in-plane curvature or out-of-plane twisting, while the other three remain planar and co-linear. While the first three appear less crystalline by X-ray diffraction, they afford a smoother solid-state film surface topology and increased electron mobility in top-gate, bottom-contact OFETs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 35 publications
3
14
0
Order By: Relevance
“…The TVT units have already been known to be useful for constructing planar D–A polymer, because the vinylene unit is less likely to be twisted and energetically favors a 2D conformation. Interestingly, although the BT unit contains a single bond, the CC bond between the two thiophene rings of bithiophene is not remarkably twisted and the overall planarity of PIIG–BT was found to be similar to PIIG–TVT. Both of the polymers had a small dihedral angle (9.9°–13.8°) at the D–A bond and an even smaller torsion angle (0.2°–2.2°) inside the donor units.…”
Section: Resultsmentioning
confidence: 99%
“…The TVT units have already been known to be useful for constructing planar D–A polymer, because the vinylene unit is less likely to be twisted and energetically favors a 2D conformation. Interestingly, although the BT unit contains a single bond, the CC bond between the two thiophene rings of bithiophene is not remarkably twisted and the overall planarity of PIIG–BT was found to be similar to PIIG–TVT. Both of the polymers had a small dihedral angle (9.9°–13.8°) at the D–A bond and an even smaller torsion angle (0.2°–2.2°) inside the donor units.…”
Section: Resultsmentioning
confidence: 99%
“…McCulloch’s group reported a series of isoDPP-polymers (P22–26, Figure 6) [75]. The UV/vis absorption maxima of all polymers in thin film located between 620 and 650 nm except P25 and P26 being of 687 and 554 nm, respectively.…”
Section: Polymersmentioning
confidence: 99%
“…The charge carrier mobility of polymers with trans -vinylene and thiophene-derived repeating units ( trans -poly­(thienylenevinylene)­s; PTVs) has been reported to be the highest among π-conjugated polymers. However, trans -PTVs have strong interchain π–π interactions due to their planar structure, which limits their solubility. , The more twisted configuration of the cis -vinylene units tends to result in less optimized interchain stacking and thus higher solubility . We have demonstrated that thin films of cis -poly­( p -phenylenevinylene)­s undergo cis-to-trans isomerization under UV irradiation (Figure e). A similar isomerization of cis -vinylene may provide a direct and efficient route to the fabrication of trans -PTVs thin films (Figure f).…”
Section: Introductionmentioning
confidence: 98%
“…16−22 However, trans-PTVs have strong interchain π−π interactions due to their planar structure, which limits their solubility. 20,21 The more twisted configuration of the cis-vinylene units tends to result in less optimized interchain stacking and thus higher solubility. 23 We have demonstrated that thin films of cis-poly(pphenylenevinylene)s undergo cis-to-trans isomerization under UV irradiation (Figure 1e).…”
Section: ■ Introductionmentioning
confidence: 99%